SCREENING OF ACTINOMYCETES ISOLATED FROM NATURAL ECOSYSTEM (PERIYAR TIGER RESERVE, KERALA) FOR LIPASE INHIBITORY ACTIVITIES - DIKSHA KUMARI; DEEPU SURENDRAN; ESLIN KHYMDEIT; VENKATA KRISHNA BAYINENI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present study was undertaken to screen pancreatic lipase inhibitory activity of crude extracts of actinomycetes species isolated from the soil sediments of Periyar Tiger Reserve, Kerala. The identified lipase inhibitory activity was partially purified, and the selected isolate was identified by 16S rRNA sequencing. Methods: The preliminary screening for the extracellular lipase inhibitory activities of actinomycetes isolates was performed by inoculating the culture to the test tubes containing inoculation media in submerged condition. The lipase inhibitory activities were again evaluated based on secondary screening on the production media and the strain which produced consistent highest lipase inhibitory activity was selected for further studies. The crude extract from the selected strain was subjected to solvent extraction and partially purified by plain silica gel column (mesh size 100–200 μm; column 300 mm×18 mm) and eluted with different solvents in the increasing order of polarity and all the solvent fractions were checked for lipase inhibitory activity. Results: Based on the secondary screening on the production of media, DDE6 strain showed highest lipase inhibitory activity (96.2%) and was selected for further studies. The dichloromethane extract showed the highest lipase inhibitory activity (96.38%) when compared to other solvents. The partial 16S rRNA sequence analysis of DDE6 isolate confirmed the strain as Curtobacterium oceanosedimentum. Conclusion: Many research publications have reported the isolation of Curtobacterium species and its type strains. However, this is the first time to report its potential to produce lipase inhibitor metabolite under submerged fermentation conditions. Further, studies are needed to be conducted to characterize the active principle of lipase inhibition as well as to elucidate the structure of the extracted compound.